SIFAT PULP SULFAT KAYU KURANG DIKENAL ASAL JAWA BARAT - Rena M Siagian; Setyani B Lestari; Yoswita Yoswita (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
This paper deals with the results of a laboratory-scale manufacture of sulphate pulp from lesser known wood species from West Java in the possible utilization as a raw material for pulp with the emphasizes on yield, pulp processing properties and physical properties. There arefive wood species experimented, i.e. marasi (Hymenaea courbaril L.), asam jawa (Tamarindus indica L.), balobo (Diplodiscus (?), kundang (Ficus variegata Bl.) and kendal (Ehretia acuminata R.Br.).The results revealed that marasi, asam jawa, kundang, and kendal wood species could produce pulp with the yield commonly in the range as obtained from sulphate process, i.e. 40 - 55 percent. The lowest pulp yield (less than 40 percent), however, was obtained by balobo species. The favorable delignification with the low Kappa number in the resulting sulphate pulp only occurred to asam jawa wood species. Meanwhile, the other four wood species in the sulphate process proceeded with less favorable delignification and concurrently produced pulp with high Kappa number.When viewed from the pulp yield, Kappa number, and active alkali consumption, only asam jawa wood species seemed suitable for producing bleached pulp. Conversely, the other four species appeared to be unsuitable for bleached pulp. To acquire their suitability, hence, those four species should be cooked in the sulphate process under a more enhanced condition.The properties of the unbleached pulp from those five wood species were in the ranges of 42 -61 Nm/g for tensile index, 6.52 - 12.38 Nm2/kg for tear index, 2.47 - 3.20 KPa.m2/g for burst index, and 3.64 - 8.16 df for folding endurance.Viewed from physical properties that covered tensile, burst, and tear index, it turned out that balobo-wood (Diplodiscus (?)) pulp afforded the highest physical properties followed by those of kundang (Ficus variegata Bl.) and marasi (Hymenaea courbaril L.) wood species. Meanwhile, the lowest physical properties of the pulp sheet were obtained from asam jawa (Tamarindus indica L.) and kendal (Ehretia acuminata R.Br.) woods.